UPAYA PENINGKATAN PRESTASI BELAJAR MELALUI PENGEMBANGAN CONTEXTUAL TEACHING AND LEARNING (CTL) DENGAN STRATEGI BERTANYA BERBASIS MASALAH-MASALAH SOSIAL DI LINGKUNGAN SMKN 4 RAMBAH - Yasmalinar Yasmalinar (JURNAL PENDIDIKAN ROKANIA, 2019)
The purpose of this study is to examine and get a picture of the use of the Contextual Teaching And Learning (CTL) approach through questioning strategies that are based on social problems in the environment of students in class X Dressmaking 4 Rambah SMKN. The method used in this research is the Classroom Action Research (CAR) method. The results of this study with Contextual Teaching And Learning (CTL) in learning history through questioning strategies that are based on social problems in the environment of students in class X Clothing for SMKN 4 Rambah are divided into four steps: the first step, before taking action the researcher tries to recognize the character first class. Because after recognizing the character of the class will facilitate the learning process. The class X character of Clothing can be called quite active. Students actively answer questions from the teacher regarding historical facts. By developing CTL through questioning strategies that are based on social problems in the student environment, students have an understanding and sensitivity to the problems around them in addition to understanding historical material in the form of facts and event descriptions. The second step, at the beginning of learning the teacher must first direct and explain to students that by learning history that is connected with the present can provide benefits and meaning for everyday life. This is done so that students are not confused by the application of CTL that is applied by the teacher. In addition, to increase student activity the teacher must motivate students to learn actively during the learning process.